Astrocyte-Neuron Signaling in Synaptogenesis - Shan, Lili; Zhang, Tongran; Fan, Kevin; Cai, Weibo; Liu, Huisheng (Frontiers in Cell and Developmental Biology, 2021)
Astrocytes are the key component of the central nervous system (CNS), serving as pivotal regulators of neuronal synapse formation and maturation through their ability to dynamically and bidirectionally communicate with synapses throughout life. In the past 20 years, numerous astrocyte-derived molecules promoting synaptogenesis have been discovered. However, our understanding of the cell biological basis underlying intra-neuron processes and astrocyte-mediated synaptogenesis is still in its infancy. Here, we provide a comprehensive overview of the various ways astrocytes talk to neurons, and highlight astrocytes' heterogeneity that allow them to displays regional-specific capabilities in boosting synaptogenesis. Finally, we conclude with promises and future directions on how organoids generated from human induced pluripotent stem cells (hiPSCs) effectively address the signaling pathways astrocytes employ in synaptic development.